Implementasi Metode Contextual Teaching and Learning (CTL) Pada Pembelajaran Al-Qur’an Hadist Siswa Kelas X-A MAN 3 Banyumas - Aprilliani, Nindy (Sekolah Tinggi Agama Islam (STAI) AL-IKHLAS DAIRI SIDIKALANG, 2025)
Education is a guideline for every human development. The main problem is choosing a spesific direction and goal. In education, an approach is needed including curriculum renewal, quality of learning an the effectiveness of the learning methods used. Teaching and learning activities in the classroom need to be carried out as well as possible so that educational goals can be achieved. Seeing the low interest of students in studying the Qur’an and Hadith, an interesting and enjoyable learning method is needed. One of them is the Contextual Teaching and Learning (CTL) learning method. The study aims to describe the implementation of the Contextual Teaching and Learning (CTL) method in learning the Al-Qur’an Hadith of class X students of MAN 3 Banyumas. The research method used is field research with a qualitative descriptive approach. Data collected in this study through observation, interviews and documentation. Data analysis was carried out with the steps of data collection, data reduction and drawing conclusions. The result of the study showed that the implementation of the Contexual Teaching and Learning (CTL) method uses learning steps contained in the 5 (five) relavant Contexual Teaching and Learning (CTL) learning components. Including constructivism, modelling, inquiry (finding for yourself), questioning, learning community. Al-Qur'an Hadith learning activities in the application of the Contextual Teaching and Learning (CTL) method include students developing new knowledge that they already have, studying the material in the Al-Qur'an Hadith book, student involvement in discussion and question and answer activities, forming study groups, making sketches or models for learning needs, conducting learning reflections and teachers conducting objective evaluations of students